Cost-effectiveness and clinical outcomes of intermittent/continuous proton pump inhibitors infusion in high bleeding risk of ulcers: A retrospective observational cohort study. Issue 49 (10th December 2021) - Hsieh, Hui-Hsia; Wu, Tien-Yuan; Chen, Chi-Hua; Hour, Mann-Jen
Abstract : Abstract: The purpose of this study was to evaluate the clinical outcomes, including patient prognosis and medication expense, of proton pump inhibitors administered by high-dose continuous infusion (HDC, 80 mg loading dose, then 8 mg/h for 72 hours) or non-high-dose intermittent infusion (NHDI, 40 mg qd or 40 mg q12 h, for 3 days) regimens in high-risk patients with bleeding peptic ulcers. In this retrospective cohort study, patients with peptic ulcers and endoscopic hemostasis between January, 2013 and December, 2015 were included. The primary endpoints were rebleeding and mortality rates within 7 days. The secondary endpoints were length of stay (LOS), transfusion units of packed red blood cells (PRBCs), and the number needed to treat. A total of 335 patients met the inclusion criteria during the 3-year follow-up period. The cumulative incidence of rebleeding within 7 days was 20.4% and 11.2% in the HDC and NHDI groups, respectively, with a significant difference ( P  = .021). The mortality rate was 12.1% and 7.3% in the HDC and NHDI groups, respectively, with no significant difference ( P  = .136). Univariate Cox proportional hazards model analysis showed that the risk of rebleeding within 7 days in the HDC group was higher than that in the NHDI group. The hazard ratio for HDC vs. NHDI was 1.93 ( P  = .021). There were significant differences in LOS ( P  = .034) and PRBC units ( P  = .005) for risk of rebleeding within 7 days, as well as in transfusion units of PRBCs for mortality rate analysis ( p  < 0.001), between the HDC and NHDI groups. The results showed that the NHDI regimen could reduce the risk of rebleeding within 7 days in 1 of 11 patients (number needed to treat = 11) and could reduce medication cost by US$ 400 to 800. The NHDI regimen showed a lower risk of rebleeding within 7 days, shorter LOS, and fewer PRBC units than that of the HDC regimen. Receiving NHDI has better cost-effective outcomes than that of HDC for patients with high-risk bleeding peptic ulcers.